p38 Mitogen-Activated Protein Kinase의 억제를 통한 진세노사이드 Rg3의 Thromboxane A₂ 억제 효과 - 권혁우(Hyuk-Woo Kwon) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
G-Rg3는 인삼의 성분으로서 많은 효과가 밝혀졌지만, 혈소판에서의 억제 기작에 대한 연구는 미흡하다. 본 연구에서는 G-Rg3가 혈소판에서 합성되어 분비되는 TXA2의 생산에 관여한다고 알려진 효소인 COX-1, TXAS와 신호전달 분자인 p38 MAPK, cPLA2의 인산화를 어떻게 조절하며 혈소판 응집을 억제시키는지 규명하고자 하였다. 그 결과 G-Rg3는 thrombin이 유도한 혈소판 응집을 강력하게 억제하였고, p38 MAPK, cPLA2의 인산화와 COX-1, TXAS의 활성을 감소시키며 arachidonic acid 분비와 TXA2의 합성을 농도 의존적으로 억제하였다. 또한 G-Rg3는 thrombin이 촉진시킨 p38의 인산화를 억제함으로써 과립방출의 지표인 ATP와 serotonin의 방출을 억제하였다. 따라서 G-Rg3는 인체혈소판에서 TXA2의 생성을 억제함으로써 혈소판 응집억제를 나타내는 치료 및 예방약물로서 유용한 가치가 있다고 여겨진다. Thromboxane A2 plays a central role in hemostasis and thrombus formation, which stimulates other platelets as an agonist leading intracellular signaling cascades. In this study, we tried to explain the inhibitory mechanism of 20(S)-ginsenoside Rg3 (G-Rg3) on thromboxane A2 production by assaying the activities of TXA2 production-associated microsomal enzymes and associated signaling molecules. Thrombin-stimulated human platelet aggregation was dose-dependently decreased by G-Rg3 and attenuated thromboxane A2 production via down regulation of microsomal cyclooxygenase-1 and thromboxane A2 synthase activities. In addition, arachidonic acid release, which is a precursor of TXA2 was decreased by G-Rg3 through dephosphorylation of cytosolic phospholipase A2 and p38 mitogen-activated protein kinase. Overall, the results revealed the specific signaling pathway of TXA2 production via G-Rg3. Therefore, G-Rg3 is a beneficial novel compound inhibiting TXA2 production, which may prevent platelet aggregation-mediated thrombotic disease. KCI Citation Count: 0